2015
DOI: 10.1121/1.4904501
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the vibroacoustic properties of plates with embedded grids of acoustic black holes

Abstract: The concept of an Acoustic Black Hole (ABH) has been developed and exploited as an approach for passively attenuating structural vibration. The basic principle of the ABH relies on proper tailoring of the structure geometrical properties in order to produce a gradual reduction of the flexural wave speed, theoretically approaching zero. For practical systems the idealized "zero" wave speed condition cannot be achieved so the structural areas of low wave speed are treated with surface damping layers to allow the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(91 citation statements)
references
References 7 publications
1
90
0
Order By: Relevance
“…Experimental evidences of the eect are numerous [10,11,12]. While it is very ecient at high frequencies, several works point out the ineciency of the ABH technique in the low frequency regime [9,13], which may be a drawback in its potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidences of the eect are numerous [10,11,12]. While it is very ecient at high frequencies, several works point out the ineciency of the ABH technique in the low frequency regime [9,13], which may be a drawback in its potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…ABH effect attracts increasing attention as a promising passive vibration control method because vibration energy can be channeled and only a very small amount of damping materials is required at the energy focalization region to achieve efficient damping to flexural waves [4][5][6][7][8][9]. It also shows appealing potential in sound radiation control [10,11] and energy harvesting [12,13] due to the high energy concentration within a confined area. Krylov et al [3] showed that the inevitable truncation (the residual thickness at the wedge tip) resulting from the manufacturing difficulty would significantly compromise the ideal ABH effect by generating wave reflections.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization results also show that ABH vibration reduction can be achieved at frequencies lower than expected by the wavelength smaller than the taper length limit (k b < x L ) defined by Conlon et al 4 For the aluminum taper length of 20 cm, this occurs at 243 Hz. However, these results are achieved only when NWV is significantly violated (see objective 2 of Fig.…”
Section: Discussionmentioning
confidence: 78%
“…[1][2][3][4] By introducing a power-law taper in a beam, the wavespeed will approach zero as the beam thickness decreases and a wave will never reflect back into the beam once it enters the taper. Higher-power tapers have been shown to have a lower total reflection coefficient and therefore better performance.…”
Section: Introductionmentioning
confidence: 99%